Habit and ecology of the Petriellales, an unusual group of seed plants from the triassic of Gondwana - Bomfleur, Benjamin; Decombeix, Anne Laure; Schwendemann, Andrew; Escapa, Ignacio Hernan; Taylor, Edith L.; Taylor, Thomas N.; McLoughlin, Stephen (International Journal of Plant Sciences)
Premise of research. Well-preserved Triassic plant fossils from Antarctica yield insights into the physiology of plant growth under the seasonal light regimes of warm polar forests, a type of ecosystem without any modern analogue. Among the many well-known Triassic plants from Antarctica is the enigmatic Petriellaea triangulata, a dispersed seedpod structure that is considered a possible homologue of the angiosperm carpel. However, the morphology and physiology of the plants that produced these seedpods have so far remained largely elusive. Methodology. Here, we describe petriellalean stems and leaves in compression and anatomical preservation that enable a detailed interpretation of the physiology and ecology of these plants. Pivotal results. Our results indicate that the Petriellales were diminutive, evergreen, shade-adapted perennial shrubs that colonized the understory of the deciduous forest biome of polar Gondwana. This life form is very unlike that of any other known seed-plant group of that time. By contrast, it fi ts remarkably well into the "dark and disturbed" niche that some authors considered to have sheltered the rise of the fl owering plants some 100 Myr later. Conclusions. The hitherto enigmatic Petriellales are now among the most comprehensively reconstructed groups of extinct seed plants and emerge as promising candidates for elucidating the mysterious origin of the angiosperms. Fil: Bomfleur, Benjamin. Swedish Museum of Natural History; Suecia Fil: Decombeix, Anne Laure. Universite Montpellier II; Francia Fil: Schwendemann, Andrew. Lander University; Estados Unidos Fil: Escapa, Ignacio Hernan. Museo Paleontológico Egidio Feruglio; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Taylor, Edith L. University of Kansas; Estados Unidos Fil: Taylor, Thomas N. University of Kansas; Estados Unidos Fil: McLoughlin, Stephen. Swedish Museum Of Natural History; Suecia